A critical analysis of the discourses on Muslims in the media before and after the events of September 11, 2001 - Ebrahim, Hanifa (My University, 2008)
This research explores the discourses of Muslims that had emerged in The Star, Daily News, Cape Argus and New York Times before and after the bombings of the New York City’s World Trade Centre Towers on September 11, 2001. This was a qualitative study that analysed a total of 176 articles from the various newspapers from July 2001 to November 2001. A discourse analytic approach was used as the method of analysis within a broad depth hermeneutic framework. The depth hermeneutic approach emphasises the analysis of the socio-historical context in order to understand how certain constructions of Muslims had historically emerged. Therefore, this study traces the construction of Muslims and the media historically. The results indicate that the dominant discourses of Muslims that have emerged are that ‘Muslims are fundamentalists’, ‘Muslims are violent’, ‘ Muslims cannot be trusted’ and the depiction of Muslims in conflicting terms in relation to the West, namely: ‘Muslims versus the Western World’. The various sub-themes that had emerged are as follows; ‘Muslims are a force to be feared,’ ‘Islam teaches violence’ and that ‘Muslims are inhumane and uncivilised. The ideological representation of Muslims within the texts as the out-group when compared to the West is emphasised through these discourses. A comparison of the various newspapers portrayal of Muslims in the media before and after September 11, 2001, shows that the Cape Argus depicts a more positive representation of Muslims in both instances. The findings reveal that Daily News, The Star and the New York Times present a more negative view of Muslims before and after the events of September 11, 2001.
Keywords: Muslims; discourse analysis; September 11, 2001; media